Cytomorphological Findings of Thyroid Lesions Based on theBethesda System and Their Relation with Thyroid Hormonal Status:A Cross-Sectional Study - Khadka, Rajya; Shrestha, Hari Govinda; Karmacharya, Kavita; Parajuli, Ganesh; Shrestha, Rajesh; Adhikari, Ashish; Shrestha, Ujwal; Pradhan , Dipendra (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Swelling of the thyroid gland is a common presentation of thyroid diseases, both benign and malignant, and some are associated with thyroid dysfunction. Fine needle aspiration cytology, along with ultrasound and assessment of thyroid function status, remains the mainstay of evaluation of thyroid swellings. This study aimed to classify thyroid lesions according to the Bethesda system and to assess their relationship with thyroid hormonal status. Methods: A cross-sectional study was conducted prospectively from April 2023 to April 2024 in a tertiary care center after ethical clearance from the Institutional Review Committee (Reference number: 774). Patients with thyroid lesions were included using convenience sampling, with a sample size of 141. Fine needle aspiration cytology was performed for lesion classification. Data entry and analysis were done using Microsoft Excel and Statistical Package for Social Sciences version 20. Results: Among 141 cases, the most common thyroid lesion diagnosed on fine needle aspiration cytology was benign, comprising 87 (61.70%), with benign follicular nodule accounting for 63 (44.70%) among the benign lesions. Among all, 99 (70.23%) patients presented with euthyroid status, and no statistical correlation between thyroid hormone status and benign versus malignant lesions or Bethesda classification was seen in this study. In total, 120 (85.11%) were female. The age group ranged from 18 to 87 years, and the mean age at presentation was 54.8 years. Conclusions: In this study most thyroid lesions fell into the Bethesda category II. Thus, fine needle aspiration cytology is an important diagnostic tool for thyroid lesions. However, thyroid hormone status and benign versus malignant lesions showed no statistical correlation.